Strategic HR Orientation of Companies in India: A Content Analysis Approach - Sharma, J. K.; Shukla, Shalini (Prabandhan: Indian Journal of Management, 2015)
This study used the content analysis approach for analyzing the strategic orientation of companies in India. Recognizing that HRM is no longer an administrative function alone, but assumes strategic importance affecting direction and future potential of any organization, this paper attempted to examine the extent of attention and focus to management of human resources as reflected in the public disclosures by the companies. Using the Economic Times Intelligent Group (ETIG) database of top 500 companies in India, equal numbers of domestic as well as foreign companies identified on the basis of shareholding pattern were analyzed through content analysis of their annual reports. The indicators used to measure the importance included space and coverage to HR issues, future plans and investment related to HR, and communication of HR focus through key HR personnel. These indicators were then linked to dimensions such as administrative activity, employee advocacy and support, change management, competency, strategic development, and employee partnership. The findings highlighted that HR as a strategic asset does not significantly reflect in annual reports of Indian companies. Significant differences were observed in orientation towards HR between domestic and foreign companies operating in India. The results showed no direct linkage between HR orientation as reflected in annual reports with profit after tax, but found a significant relationship with an increase in market capitalization. The study has important implications for HR professionals and strategic leaders in their endeavors to create value.